THE VISUAL IMAGE OF THE TEACHER: A COMPARATIVE STUDY - Kestere, Iveta; Wolhuter, Charl; Lozano, Ricardo (Acta Paedagogica Vilnensia, 2013)
The paper is a compilation of research in ten countries – England, South Africa, Serbia, Slovenia, Greece, Bulgaria, Latvia, Turkey, Pakistan, and Mexico. Pupils and teachers in these countries were asked what does a typical teacher look like, and a unified methodology was used to analyze the results. The participants’ written and drawn responses reveal similarities and contrasts in teacher and pupil perceptions of the typical teacher, as well as similarities and differences among countries. Unexpected results reveal teacher and pupil perceptions of the ideal teacher, as well as descriptions of both good and bad teachers.